Dinamika Tradisi Tironan Pada Masyarakat Desa Sonorejo Bojonegoro (1998-2023) - Rahayu, Indah; Ayundasari, Lutfiah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Tironan tradition is one of the traditions of the people of Bojonegoro District, especially in the Sonorejo Village. Tironan tradition is a tradition to commemorate a person’s birthday based on the calculation of the java calendar. This tradition is still carried out by the Sonorejo Village community with aim of respecting and preserving the ancestral heritage. Moreover, the community pursues this tradition with the aim of asking for help, being removed from danger, and being given happiness in life. In its implementation, the tironan tradition has Islamic values contained in it such as a form of people’s gratitude to God, form of mutual compassion, and form of solidarity to keep arms of mercy between neighbours. The aim of the research was to learn about the procession and the Islamic values contained in the tironan traditions in the Sonorejo Village, as well as to learn about the change in the tironan tradition in the Sonorejo Village from 1998 to 2023. This research is to determine the changes in the tironan tradition that occurred in Sonorejo Village in 1998 due to the monetary crisis, while in 2023 there was an improvement in various areas of the economy. This research uses descriptive qualitative methods, which use data collection techniques with observation, interviews, literature studies, and documentation. The results of this study show that there is a change in the tironan tradition in the Sonorejo Village. Although the tironan tradition still exists to this day, there have been some changes in its implementation such as the ubarampe presented, the procession its execution, and the perpetrators of the tironan tradition. The changing times of increasing modernity, and the lack of public awareness in preserving them, as well the assumption that they are ancient and inconsistent with religious teachings (commiting idolatrous acts).